To create a perfect square trinomial, halve the x coefficient, square it, and then add that value.
In the case of x² + 6x, we would have 6 to get 3, then square 3 to get 9.
We would add 9 to make a perfect square trinomial.
<u>
</u><u>Why this works</u>
A perfect square trinomial is designed to factor to some value (x+n)².
When you FOIL this you get x² + 2nx + n².
As you can see, if you wanted to find the value of that n², you could take that x coefficient 2n, halve it to get n, and then square it to get n²!
Equal? I don’t rlly understand what this means
Answer:
x = 3
Step-by-step explanation:
Here, we want to find the value of x
By mathematical convention;
NM = NL + LM
Now, substitute individual values
3x + 13 = (6x-5) + (2x + 3)
3x + 13 = 6x-5 + 2x + 3
3x + 13 = 8x -2
Collect like terms
8x -3x = 13 + 2
5x = 15
x = 15/5
x = 3
<h2>
Answer: 1/5 or 0.2
_____________________________________</h2><h3>
Isolate the variable by dividing each side by factors that don't contain the variable.
Exact Form: x = 1/5
Decimal Form:
x = 0.2</h3><h3>
______________________________________________</h3>
Hope this helps!
Also can I please have Brainliest...?
<em>Only if I'm right of course...</em>